Broadband photocurrent enhancement in a-Si:H solar cells with plasmonic back reflectors - Morawiec, Seweryn (2018)
The authors acknowledge Francesco Ruffino for the AFM measurements. This work was funded by the EU FP7 Marie Curie Action FP7-PEOPLE-2010-ITN through the PROPHET project (Grant No. 264687), the bilateral CNR/AVCR project "Photoresponse of nanostructures for advanced photovoltaic applications", the MIUR project Energetic (Grant no. PON02_00355_3391233) and by the Portuguese Science Foundation (FCT-MEC) through the Strategic Project PEst-C/CTM/LA0025/2013-14 and the research project PTDC/CTM-ENE/2514/2012.